Choice of route of hysterectomy and vaginal-laparoscopic surgical training – initial report - Klimczak, Krzysztof; Katulski, Jarosław; Malinowski, Andrzej; Dejewski, Cezary (Menopause Review/Przegląd Menopauzalny, 2007)
Objectives and study design: The aim of the study was to evaluate the choice of the route of hysterectomy in all the operations performed in the Department of Gynaecology, Tuchola District Hospital, from 15.05.2005 to 16.05.2007. According to the abstract of Prof. A. Malinowski (Gin Pol, 2007, 78, 1), the study was classified as an initial report. Material and methods: The statistical data from the one-year period (16.05.2006–16.05.2007) when the intensive training of gynaecologists was introduced were compared to the previous one-year period (15.05.2005–15.05.2006), when no training was performed. The analysis concerned all the hysterectomies performed abdominally (AH), vaginally (VH), with laparoscopic assistance (LAVH) and laparoscopically (LTH), due to benign diseases. Results: In the one-year period preceding the onset of intensive training (15.05.2005–15.05.2006), 61 hysterectomies were performed: 43 abdominal (70.5%) and 18 vaginal (29.5%). In the one-year period when the training was introduced (16.05.2006–16.05.2007), 77 hysterectomies were performed: 16 abdominal (20.8%), 44 vaginal (57.1%), 13 laparoscopically assisted (16.8%) and 4 laparoscopic total hysterectomies (5.3%). As a result, the proportion of vaginal to abdominal hysterectomies was reversed. Nevertheless, laparoscopic total hysterectomy was performed for the first time in Tuchola Hospital, in the “training period”. Conclusions: 1. The continuous and systematic surgical training revealed vaginal hysterectomy as the dominant route of hysterectomy chosen by surgeons. 2. The reversal of the percentage of abdominal and non-abdominal (VH, LAVH, LTH) way of hysterectomy was realized in one year of intensive training